Increasing health facility childbirth in Ghana: the role of network and community norms - Leslie E. Cofie; Clare Barrington; Kersten Cope; Catherine E. LePrevost; Kavita Singh (BMC, 2023)
Abstract Background Reducing pregnancy-related deaths in Sub-Saharan Africa through increases in health facility births may be achieved by promoting community norms and network norms favoring health facility births. However, the process of how both norms shift attitudes and actions towards facility delivery is little studied. We examined the association of network and community norms with facility birth, following a quality improvement intervention to improve facility births in Ghana. Methods A 2015 mixed methods evaluation of a Maternal and Newborn Health Referral (MNHR) project in Ghana included a cross-sectional survey of women (N = 508), aged 15-49 years; in-depth interviews (IDIs) with mothers (n = 40), husbands (n = 20) and healthcare improvement collaborative leaders (n = 8); and focus group discussions (FGDs) with mothers-in-law (n = 4) and collaborative members (n = 7). Multivariable logistic regression was used to examine the association of network and community norms with facility birth. Thematic analysis of the qualitative data was conducted to explain this relationship. Results The network norm of perceived family approval of facility delivery (AOR: 5.54, CI: 1.65-18.57) and the community norm of perceived number of women in the community that deliver in a facility (AOR: 3.00, CI: 1.66-5.43) were independently associated with facility delivery. In qualitative IDIs and FGDs both norms were also collectively perceived as influencing facility delivery. However, network norms were more influential in women's utilization of facility-based pregnancy-related care. Healthcare improvement collaboratives were important in swaying both network and community norms toward facility-based delivery by offering pregnancy-related health information, antenatal care, and support for facility delivery. Conclusion Quality improvement initiatives impact both community and network norms. To be most impactful in advancing facility-based pregnancy-related care, these initiatives should focus on highlighting the shifting trend toward facility delivery in rural communicates and promoting support for facility delivery among women's personal networks.